Altered vision in MSM patient, diagnosis of ocular syphilis in primary care: a case report - Ali, Hanifatiyah; Ali, Mohd Fairuz; Ahmad Tarmidzi, Nor Azita; Raja Othman, Raja Nor Farahiyah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
There is a concern in the emergent of sexually transmitted diseases and its complication with the increase in the prevalence of men who have sex with men (MSM). Ocular syphilis is one of the conditions that is associated with high-risk patients especially in patients already infected with human immunodeficiency virus (HIV). This case reports an MSM patient who was diagnosed with concurrent HIV and ocular syphilis infections. The report focuses on the clinical presentation of ocular syphilis in HIV infected patients and its management in primary care.